1993
DOI: 10.1103/physrevlett.70.441
|View full text |Cite
|
Sign up to set email alerts
|

Beam divergence with harmonic gyroresonance in focusing wiggler and axial field

Abstract: The transport of a relativistic electron beam was studied experimentally and numerically in a magnetic field configuration which consists of a focusing wiggler as well as an additional axial guide field. A new beam divergence was found for the lower side of the magnetoresonance. It was identified as due to the effect of the second harmonic mode of the cyclotron frequency in the resonance, determined by /jft i i -A^rn for n =2. The harmonic resonance was detected for the planar wiggler first, and it could appea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 10 publications
2
11
0
Order By: Relevance
“…Although, as mentioned at the beginning of this article, a number of approaches to the linear theory of a hybrid FEM have been already formulated, a new one presented here allowed us to both provide a consistent and unified analytical description of electron dynamics for all values of the guide magnetic field and, more importantly, to find an efficient characterization of the dynamical chaos present in the system. It is also worth mentioning that the zones of suppressed beam transport found in [12] are in good correspondence with our (semi)analytical calculations for the zones of dynamical chaos (cf. Fig.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Although, as mentioned at the beginning of this article, a number of approaches to the linear theory of a hybrid FEM have been already formulated, a new one presented here allowed us to both provide a consistent and unified analytical description of electron dynamics for all values of the guide magnetic field and, more importantly, to find an efficient characterization of the dynamical chaos present in the system. It is also worth mentioning that the zones of suppressed beam transport found in [12] are in good correspondence with our (semi)analytical calculations for the zones of dynamical chaos (cf. Fig.…”
Section: Discussionsupporting
confidence: 88%
“…This is achieved because the method of Lindshtedt employed by us to obtain test individual electron trajectories in the magnetostatic field of a hybrid planar FEM is capable of high precision in analytical calculations. It should be also mentioned that this method is sufficiently general to be applicable to describe the motion of charged particles in spatially inhomogeneous static magnetic fields like, for example, that in [12,29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To further increase the beam current, Sakamoto et al [3] superposed an axial guiding field on the selffocusing wiggler and demonstrated the advantages of this configuration. Meanwhile, they also observed a deterioration of beam propagation due to the resonance between the wiggler and cyclotron motions.…”
mentioning
confidence: 99%